(untitled) (SP Swag: Sudur Paschim Wisdom of Academic Gentry Journal, 2025)
Municipal waste management has become increasingly difficult due to rapid urbanization, internal migration, and unplanned settlements in municipalities. These challenges place a significant burden on municipal administrations to review and update their plans and strategies for effective waste management. This study analyzes the waste management practices and initiatives aimed at achieving zero waste in Bheemdatt Municipality by employing key informant interviews, field observations, and policy analysis methods. The findings indicate that the municipality has engaged a private waste management service provider to collect municipal waste from selected residential areas. Together, the municipality and the private company manage an average of six tons of solid waste daily. However, the final disposal of municipal waste is neither environmentally sustainable nor economically viable. A SWOT analysis reveals several strengths, including a decentralized government structure, endorsement of waste management policies, and strong community involvement. These factors support regional and participative approaches towards a zero-waste mechanism. Conversely, poor operational efficiency remains a major challenge due to inadequate infrastructure, lack of integrated solid waste management (ISWM) components, insufficiently skilled human resources, financial constraints, weak institutional capacity, and poor source segregation of waste. To manage municipal waste effectively and promote the zero-waste goal, opportunities exist to improve system efficiency, foster public-private partnerships, and enhance community awareness.